Social and Environmental Assessment to Promote Sustainability : An Informal View from the World Bank - Goodland, Robert (World Bank, Washington, DC, 2014)
This report compares the history of Environmental Assessment (EA) and Social Assessment (SA) in the World Bank, in order to draw "lessons learned" to improve development. The main need-to shift attention from the EA report to implementation on the ground-has been started recently (Goodland and Mercier 1999), so this paper focuses on process. The history of social and economic assessments shows how scarce social and natural capital is being converted to abundant economic capital. The EA and SA processes are examined to see the extent to which they could promote sustainability, the maintenance of capital. This means social and economic assessments can be used to prevent inadvertent consumption of natural and social capital. Following a historical section, there is a brief but more theoretical section on the substitutability between the four main forms of capital and their relevance to achieving the goal of sustainability by means of improved social and economic assessments.